2018
DOI: 10.1111/jop.12680
|View full text |Cite
|
Sign up to set email alerts
|

O‐GlcNAcylation in oral squamous cell carcinoma

Abstract: Unlike other types of cancers, our findings demonstrate that the levels of O-GlcNAcylation are not significantly increased in OSCC tissues or in oral cancer cells and are not associated with the histological grading of OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…17,20,21,24,26,43 However, from our recent study of O-GlcNAcylation in oral cancer, the O-GlcNAc levels have not been found to be signi cantly enhanced upon increased histopathologic severities of oral squamous cell carcinoma, nor have the OGT or the OGA expressions. 44 Consistent with these ndings, the O-GlcNAc levels, the OGT or the OGA expressions were not found to be different between the two distinct clinical severities of osteosarcoma. Therefore, involvement of O-GlcNAcylation along with OGT and OGA expressions in the pathogenesis of osteosarcoma still requires further investigations.…”
Section: Discussionsupporting
confidence: 73%
“…17,20,21,24,26,43 However, from our recent study of O-GlcNAcylation in oral cancer, the O-GlcNAc levels have not been found to be signi cantly enhanced upon increased histopathologic severities of oral squamous cell carcinoma, nor have the OGT or the OGA expressions. 44 Consistent with these ndings, the O-GlcNAc levels, the OGT or the OGA expressions were not found to be different between the two distinct clinical severities of osteosarcoma. Therefore, involvement of O-GlcNAcylation along with OGT and OGA expressions in the pathogenesis of osteosarcoma still requires further investigations.…”
Section: Discussionsupporting
confidence: 73%
“…The clinical and histopathologic features of these specimens have previously been reported [24]. As controls, 10 specimens of oral tissues were collected from 10 orally and systemically healthy and non‐smoking participants, during surgical removal of third molars with bony impaction at the Oral and Maxillofacial Surgery Clinic, Faculty of Dentistry, Chiang Mai University [25]. The approval certificates (#54/2014 and #21/2017) for the use of the OSCC and oral tissues specimens in this study were granted by the Human Experimentation Committee, Chiang Mai University.…”
Section: Methodsmentioning
confidence: 99%
“…For quantitative analysis, three representative fields at ×400 magnification were captured from each section using a CCD camera (Axiocam ICc5; Carl Zeiss) attached to a microscope (Axio Imager.Z2 m; Carl Zeiss). The immunohistochemical (IHC) scores (range: 0–7) were determined using ImageJ program version 1.48 (National Institutes of Health) by combining the percentage of positively stained cells (ie, those with scores of 0–4) and the staining intensity (of those with scores of 0–3), as previously described [25]. The positive controls were OSCC sections previously shown to have immunostaining reactivity against p‐EGFR tyr1173 , p‐AKT ser473 , and ADAM 9 antibodies [24,25], while the negative controls were OSCC sections incubated in normal blocking serum without addition of these antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HIF-1α inhibitors can suppress the autophagy of OSCC by decreasing the expression of O-GlcNAc and O-GlcNAc transferase (OGT) and increasing the expression of O-GlcNAcase (OGA) 120 . However, in another study, the levels of O-GlcNAcylation did not increase significantly in OSCC tissues, which was also not connected with the histological grading of OSCC 121 .…”
Section: O-glcnac Mediates Hnscc Autophagymentioning
confidence: 77%